Acid-responsive CST@NPs enhanced diabetic wound healing through rescuing mitochondrial dysfunction - Xuelian Zhang; Hang Li; Yang Liu; Jie Yu; Pengfei Zhang; Peiling Yu; Yuhao Liu; Suyi Jia; Lijuan Ling; Peng Li; Lei Li; Yueyao Wang; et al. (Bioactive Materials)
Diabetic ulcers (DUs) are persistent and challenging complications of diabetes. The consequences of DUs include a decline in functional status, increased risk of infection, hospitalization, and even death. Our study revealed a significant decrease in the levels of cortistatin (CST) in the skin tissue of patients with DUs and diabetic rats. This finding led us to hypothesize that the administration of exogenous CST is an effective strategy to promote wound healing in patients with DUs. We herein successfully prepared CST-loaded pDMA-pEPEMA nanoparticles (CST@NPs) designed to exhibit localized, acid-responsive behavior for enhanced wound healing. These CST@NPs were sensitive to acidic environments, triggering the rapid release of CST. In vitro experiments showed that CST@NPs effectively alleviated oxidative stress and reduced apoptosis in human umbilical vein endothelial cells (HUVECs). Our findings further demonstrated that CST@NPs accelerated re-epithelialization of the wound, enhanced collagen deposition, and stimulated angiogenesis, while alleviating the local inflammatory response. Both in vivo and in vitro results indicate that CST@NPs possess precise and rapid response capabilities in acidic environments, ensuring effective CST release to promote diabetic wound healing. In summary, this acid-responsive nanoparticle system presents a highly efficient therapeutic strategy for the treatment of chronic diabetic wounds.